MOTIVATIONS RELIGIOUS MOVEMENT JAMAAT TABLIGH: A CASE STUDY OF PADANG CITY AND MENTAWAI ISLANDS - Supardi Dwimaputra; Yantri Maputra; Faisal Efendi; Dasrizal Dasrizal; Afrikal Candra; Ikhwanuddin Abdul Majid (Mawaizh : Jurnal Dakwah dan Pengembangan Sosial Kemanusiaan, 2025)
The Tabligh Jamaat movement aims to revive the teachings of the Prophet Muhammad, both those that are recommended and those that are obligatory, in a comprehensive and holistic manner in the lives of individuals, families, and society at large, and then invite others to do good deeds and play an active role in religious movements. Focuses motivation behind the religious movement of Jemaah Tabligh. In general, the elements to be presented in this research design are that the location chosen for this research is in city of Padang and Mentawai Islands, specifically at the headquarters or Mahalla Jamaat Tabligh. This research is a field study and is descriptive qualitative in nature. Tabligh Jamaat religious movement in the cities of Padang and Mentawai is quite encouraging and appears to be consistently active in carrying out its da'wah programs, ranging from da'wah activities in halaqah, headquarters, and khuruj programs outside the headquarters of this Jamaat, all of which are funded by personal contributions from its members. The motivation of the Tabligh Jamaat is to spread the missionary activities outside its headquarters, improve the missionary materials, maintain consistency in the missionary methods, India-Pakistan-Bangladesh (IPB), missionary work in the field of education, and Joerd/Juur. This study has only been able to provide an overview of the existence and journey of the da'wah activities. Therefore, future research will be able to uncover other aspects of the Tabligh Jamaat, such as the strong familial bonds among its members and other issues within the Tabligh Jamaat.